2010
DOI: 10.1007/s12288-010-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulins in Patients with Iron Deficiency Anemia

Abstract: Iron deficiency is a common cause of anemia worldwide. Documentation shows that these patients have impaired immunity and are prone to infections. The aim of this study was to confirm whether serum immunoglobulins change in adult nonpregnant females with iron deficiency anemia. Based on patients' clinical history, CBC results, and serum ferritin, iron and total iron binding capacity, 45 healthy patients and 45 iron deficiency anemia (hypochrom microcytic) patients were entered into this case-control study. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Some reports indicate iron depletion may be responsible for decreased HMI while others did not report any change in serum immunoglobulin in iron deficiency anemia (IDA). [ 4 6 12 13 ] We therefore, designed this study to establish the altered status of these parameters in iron deficient children at baseline and at 3 months post iron supplementation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports indicate iron depletion may be responsible for decreased HMI while others did not report any change in serum immunoglobulin in iron deficiency anemia (IDA). [ 4 6 12 13 ] We therefore, designed this study to establish the altered status of these parameters in iron deficient children at baseline and at 3 months post iron supplementation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that IL-6 is affected by iron deficiency. 7,8 Reza Keramati M et al investigated lymphocyte subsets in pre-menopausal women with iron-deficiency anaemia; 50 normal subjects and 50 IDA (hypochromic microcytic) cases were enrolled. Experimental and control anticoagulated blood samples were evaluated using flow cytometry to determine the absolute and relative numbers of various lymphocyte subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Many bodily systems are affected by anaemia, including the immune system (3), and deterioration of cell-mediated immune functions, as well as decreased levels of circulating peripheral blood T lymphocytes as a consequence of iron deficiency, has been shown in some studies (4). Although human immunoglobulin levels are not decreased in iron deficiency (5), animal studies have shown that the humoral response is quite altered (6). Macrophages play an important role in nonspecific immunity and, with the contribution of polymorphonuclear leukocytes, represent a primary defence before the activation of both cell-mediated and humoral immunity.…”
Section: Introductionmentioning
confidence: 99%